Auditory discrimination improvement in young adults by a digital auditory game-based training protocol - Sergio M-Cam; Luz Maria Alonso-Valerdi; David I. Ibarra-Zarate (PLoS ONE, 2025)
Auditory training is a technique that has demonstrated to be beneficial, improving auditory processing response as a supplement to hearing loss management. Recently, game-based training approaches have also demonstrated to increase the effect of traditional auditory training. Hence, the general aim of this work is to develop a game-based auditory discrimination training to enhance the auditory processing response and measure performance in comparison to traditional methods. The evaluation of the methods will be in three directions: (1) user experience, (2) perceptual and behavioral responses, and (3) neurophysiological performance. For this purpose, the project will be conducted as follows: (1) to develop and validate a game-based auditory discrimination training method in line with the usability level, and (2) to evaluate the auditory training in terms of method performance, and neurophysiological responses, before and after the procedure. The game-based auditory training will be focused on basic sound features discrimination tasks, which will be applied for 15 hours with 4 different modules. This will contribute to understand experience processes that yield to a better training performance.